2021
DOI: 10.7717/peerj.11128
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide-induced structural modulation of the gut microbiota in patients with type 2 diabetes mellitus

Abstract: Accumulating evidence has suggested the importance of gut microbiota in the development of type 2 diabetes mellitus (T2DM). In the present study, 40 patients with T2DM were treated with liraglutide for 4 months. Feces samples and clinical characteristics were collected from these 40 T2DM patients before and after the liraglutide treatment. The diversity and composition of gut microbiota in the two groups were determined by sequencing the V4 region of bacterial 16S rRNA genes. Meanwhile, blood glucose, insulin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 43 publications
2
41
1
Order By: Relevance
“… 88 Liraglutide, which was approved by the FDA, in the application of T2DM was found to be associated with the reduction of gut microbial alpha diversity and the alteration of community distribution and the microbial interaction network. 89 Meanwhile, another GLP-1 analog, exendin-4 (Ex-4), can reduce BRB permeability, and modulate the inflammatory response to LPS as well as inhibit NF-κB activation. 90 Recently, it has been shown that GLP-1 intervention reduces the levels of NADPH oxidase 3 (NOX3), superoxide dismutase 2 (SOD2), caspase3 and light chain 3B (LC3B), while it activates the expression of B-cell lymphoma 2 (Bcl-2) in retina of type 2 diabetic rats, which suggests that GLP-1 treatment can alleviate apoptosis and autophagy of retinal cells.…”
Section: Hypothesis That Gut Microbiota Cause Drmentioning
confidence: 99%
“… 88 Liraglutide, which was approved by the FDA, in the application of T2DM was found to be associated with the reduction of gut microbial alpha diversity and the alteration of community distribution and the microbial interaction network. 89 Meanwhile, another GLP-1 analog, exendin-4 (Ex-4), can reduce BRB permeability, and modulate the inflammatory response to LPS as well as inhibit NF-κB activation. 90 Recently, it has been shown that GLP-1 intervention reduces the levels of NADPH oxidase 3 (NOX3), superoxide dismutase 2 (SOD2), caspase3 and light chain 3B (LC3B), while it activates the expression of B-cell lymphoma 2 (Bcl-2) in retina of type 2 diabetic rats, which suggests that GLP-1 treatment can alleviate apoptosis and autophagy of retinal cells.…”
Section: Hypothesis That Gut Microbiota Cause Drmentioning
confidence: 99%
“…Similarly, the same effect and mechanisms have been documented and confirmed in vivo [ 33 ]. Moreover, numerous studies have demonstrated that exogenous GLP-1 and PYY acutely reduce food intake in humans, which has been widely used in the treatment of T2DM[ 34 - 38 ]. Therefore, SCFAs not only contribute 5%-10% of energy to the host, but are also recognized by endogenous ligands of GPR41/43, and act as signaling molecules to participate in adjustment of energy[ 39 - 41 ].…”
Section: Metabolites Of Gut Microbiota Affect Energy Metabolismmentioning
confidence: 99%
“…As GLP-1 resistance is relatively common and gut microbiota composition varies widely among populations ( 18 ), perhaps specific gut microbial signatures determine responses to GLP-1 RA treatment. However, there are insufficient data to access relationships between gut microbiota composition and GLP-1 RA treatment efficacy ( 19 , 20 ). Therefore, in the pilot study, we analyzed gut microbiota of T2D patients treated with GLP-1 RA and determined clinical implications of gut microbiota in patients with distinct responses.…”
Section: Introductionmentioning
confidence: 99%